A Pre-Emptive Multimodal Pathway Featuring Peripheral Nerve Block Improves Perioperative Outcomes After Major Orthopedic Surgery. Issue 6 (1st October 2008) - Hebl, James R.; Dilger, John A.; Byer, David E.; Kopp, Sandra L.; Stevens, Susanna R.; Pagnano, Mark W.; Hanssen, Arlen D.; Horlocker, Terese T.
Abstract : Background and Objectives: : Patients undergoing major orthopedic surgery experience significant postoperative pain. Failure to provide adequate analgesia may impede early physical therapy and rehabilitation, which are important factors for maintaining joint range of motion and facilitating hospital dismissal. We examined the effect of a pre-emptive, multimodal, perioperative analgesic regimen emphasizing peripheral nerve block in patients undergoing total hip (THA) and total knee (TKA) arthroplasty. Perioperative outcomes and major postoperative complications were evaluated. Methods: : One hundred consecutive patients undergoing primary or revision THA or TKA using the Mayo Clinic Total Joint Regional Anesthesia (TJRA) protocol were retrospectively reviewed. The TJRA protocol is a pre-emptive, multimodal, perioperative analgesic regimen emphasizing peripheral nerve block that was jointly developed by the Departments of Anesthesiology and Orthopedic Surgery. Identified patients were matched 1:1 with historical controls undergoing identical surgical procedures with traditional anesthetic techniques. Matching criteria included patient age, gender, surgeon, date of surgery, and American Society of Anesthesiologists physical status. Patient demographics, preoperative joint range of motion, and anesthetic management were recorded for each patient. The primary study outcome was hospital length of stay. Secondary outcome variables included time to ambulation, joint range of motion, and discharge eligibility. Postoperative verbal analog pain scores (VAS), opioid requirements, side effects, and perioperative complications were also documented. Results: : One hundred patients underwent THA or TKA using the newly implemented Mayo Clinic TJRA protocol. Matched controls (n = 100) received intravenous patient-controlled analgesia with subsequent conversion to oral analgesics for postoperative pain management. TJRA patients had significantly shorter hospital lengths of stay (3.8 days v 5.0 days; P < .001), achieved discharge eligibility significantly sooner (1.7 ± 1.9 days earlier; P < .0001), and had improved joint range of motion (90° v 85°; P = .008) when compared with matched controls. TJRA patients had significantly improved postoperative analgesia, including lower VAS pain scores (postoperative day 0 through postoperative day 3; P < .001), and lower opioid requirements (postoperative day 0 to postoperative day 2; P = .04). Adverse outcomes such as postoperative urinary retention (50% v 31%; P < .001), and ileus formation (7% v 1%; P = .01) occurred more frequently among control patients. Conclusions: : Patients undergoing THA or TKA using a comprehensive, pre-emptive, multimodal analgesic regimen emphasizing peripheral nerve block may have significantly improved perioperative outcomes, and fewer adverse events, when compared with patients receiving traditional intravenous opioids during the initial postoperative period. Improved perioperative outcomes include a shortened hospital length of stay, and a significant reduction in postoperative urinary retention and ileus formation.